Exploring the Formation of Methodological Beliefs among English Teachers in Chile - Victor Birkner; Tamara Cortes; Rosa Delicio (FOUNDAE (Foundation of Advanced Education), 2023)
The purpose of this single-participant case study, conducted through purposeful sampling and semi-structuredinterviews,is to gain a deep understanding of how Chilean English teachers construct the beliefs that inform their methodology in disadvantagedcontexts.Theinvestigation was guided by the followingquestions: 1. How do teachers construct their beliefs about English language teaching methodology? 2. What types of factors are involved in the construction of those beliefs? The data were meticulously collectedand subsequently thematically analysed. The analysis identified six themes:previous experience, social interaction, teaching materials, attitudes towards mistakes, teacher self-evaluation, and challenges outside the classroom. Although the study confirms the findings of previous studies, two relevant themes, attitudes towards mistakes and challenges outside the classroom, emerged to contribute to the theoretical development of teachers’methodological beliefs. These two themes stand out as they shed light on how teachers of English in Chile maximisethe classroom time to teach Englishandtreatmistakeswith a positive attitude as a way topromote adaptability and resilience in contexts where speakingEnglish outside the schoolis extremely limited. Unlike previous studiesthat examinedclassroom dynamicsand mistakes in isolation, our study offers fresh insights into the complex world of methodological beliefs among Chilean teachers of English in disadvantagedcontexts.Future research should incorporate observations alongside interviews, increase participant numbers for deeper insights, and explore how attitudes and external challenges influence methodology beliefs in ELT